The Mineral Industry Of Alabama - Avery H. Reed (The National Institute for Occupational Safety and Health (NIOSH), 1958)
RECORD production of cement, clays, salt, sand and gravel, and stone highlighted the mineral industry of the State in 1956. Coal and iron-ore production declined owing to increased imports of foreign iron ore and decreased demand for metallurgical coke. Alabama ranked second in production of bauxite and of native asphalt, and third in output of iron ore. New developments in the State included the Citronelle oilfield and its 97 wells, which more than doubled the total production of petroleum compared with 1955. There is no question about the impetus that field has given to the oil and gas industry in Alabama, now 13 years old. The State's 4 oilfields are in southwest Alabama and its 1 gasfield is in Marion County, in the Warrior coal basin.